Salmonella serovars in food poisoning episodes recorded in Brazil from 1982 to 1991 - Hofer, Ernesto; Reis, Eliane Moura Falavina dos (Revista do Instituto de Medicina Tropical de São Paulo, 1994)
The Salmonella serovars involved in 25 food poisoning episodes which occurred in the Southeast and South of Brazil from 1982 to 1991 were identified. The most frequently detected serotype was S. Typhimurium (13/25, 52%), and the food most frequently involved in the transmission of Salmonella was homemade mayonnaise. The need to set up a permanent program of epidemiologic alert for food poisoning is emphasized.